2016
DOI: 10.1016/j.biortech.2016.07.081
|View full text |Cite
|
Sign up to set email alerts
|

Performance and microbial community of simultaneous anammox and denitrification (SAD) process in a sequencing batch reactor

Abstract: h i g h l i g h t sSimultaneous nitrogen and carbon removal was achieved in the SAD process. Contributions of anammox and denitrification to nitrogen removal were determined. Anammox and denitrifying bacteria dominated at low and high CODs, respectively. Brocadia sinica could grow with organic matter and tolerate high NO 3 À concentrations.a r t i c l e i n f o exhibited good diversity and abundance, but the diversity of anammox bacteria was less abundant. Brocadia sinica was able to grow in the presence of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 40 publications
5
12
0
1
Order By: Relevance
“…reported that the simultaneous partial nitrification, anammox and denitrification process was affected more by nitrogen loading rate (NLR) than by OLR. Li et al . reported that the SAD process was greatly affected by OLR, which was in agreement with the present work.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…reported that the simultaneous partial nitrification, anammox and denitrification process was affected more by nitrogen loading rate (NLR) than by OLR. Li et al . reported that the SAD process was greatly affected by OLR, which was in agreement with the present work.…”
Section: Resultssupporting
confidence: 94%
“…Wang et al 35 reported that the simultaneous partial nitrification, anammox and denitrification process was affected more by nitrogen loading rate (NLR) than by OLR. Li et al 21 reported that the SAD process was greatly affected by OLR, which was in agreement with the present work. These results indicated that low mannitol (≤0.2 mmol L −1 ) feeding could result in enhancement of SAD performance treating saline wastewater.…”
Section: Long-term Effect Resulting From Mannitol Addition On Sad Prosupporting
confidence: 94%
See 1 more Smart Citation
“…Another study stated that anammox also could coexist with denitrifier bacteria in a simultaneous process. Anammox bacteria dominantly existed in low carbon condition meanwhile the high carbon was favored by denitrifier (54). Presence of ammonium and nitrite become the substrates of anammox bacteria.…”
Section: Challenges In Wastewater Treatment: the Risk Of Nitrogen Formentioning
confidence: 99%
“…Anammox bacteria dominate at lower COD concentrations. More Anammox bacteria cause large ammonia removal, but little to no nitrate removal (Li, Qiang, Yu, Wang, Zhang, & Li, 2016).…”
Section: Mechanisms Of Nitrogen Removalmentioning
confidence: 99%